Transfer of Print-Based Academic Reading Strategies to On-Screen Reading - Khadawardi, Hanadi (International Journal of English Language Education, 2021)
This article contributes to the existing body of research on academic reading practices in the 21st century, by focusing on on-screen reading in the technological age. The study offers an insight into the nature of on-screen reading and reflects the authentic on-screen academic reading experiences of international postgraduate readers in the UK educational context. This was achieved by investigating participants’ reading comprehension strategies while reading on-screen academic research articles, compared with those employed when engaged in print-based reading. This study also scrutinizes L2 readers’ use of digital affordances and their use of e-resources while comprehending on-screen texts. Case study and interpretive qualitative approaches have been adopted in the present research study. Thematic and content analysis and a constant comparative method (CCM) have been applied to analyze the data. Although new on-screen reading strategies emerged from the data, the results reveal a transfer of print-based reading techniques to on-screen reading. This demonstrates a move from a traditional literacy to a digital one in which readers manipulate the strategies that they are already aware of, and are capable of, in order to read a text on-screen. Surprisingly, readers were much more effective: and employed more strategies and interacted more deeply with the printed text than with the on-screen text. The results from this study have led to the proposal of suggested models for interpreting on-screen L2 academic reading interactions. A number of pedagogical practices are suggested and recommended for preparing L2 readers for further academic study which could be equally applicable and useful for L1 academic reading instructions in the 21st century, including the reshaping of reading skills textbooks to accommodate and meet the needs of reading comprehension practices in the technological age and promoting learners’ digital academic literacy. These practices may be useful to teachers when teaching on-screen reading strategies for specific academic purposes in digital universities.